Addressing Our Nation's Toxic School Infrastructure in the Wake of COVID-19. (January 2022) - Kitzmiller, Erika M.; Drake Rodriguez, Akira
The commentary argues that we need to address the wide variance in school building quality under and after COVID-19. Evidence suggests that historical underinvestment in school facility capital and maintenance has created unhealthy school buildings across the nation. Federal funding and research is necessary to ensure that schools are healthy places for educators, families, and youth even after the pandemic ends.